Transformasi Penafsiran Al-Qur'an di Era Digital: Antara Tradisi dan Inovasi - Herman Herman; Unang Wahidin; Agus Mailana; Muhamad Priyatna (An-Nahdloh: Journal of Education and Islamic Studies, 2026)
The transformation of Qur'an interpretation in the digital age has significantly changed the landscape of Islamic knowledge, where access to interpretation is no longer limited to classical literature and formal institutions, but rather extends through digital platforms such as apps, social media, and artificial intelligence. This study aims to analyze the dynamics of the transformation of Qur'an interpretation in the digital era by highlighting the tension and synergy between traditional approaches and contemporary innovations. The methods used are a descriptive qualitative approach through literature studies, digital observation of various popular platforms, and content analysis to understand the influence of technology on users' religious understanding. The results of the study show that digitalization has a positive impact in the form of democratization of knowledge and the expansion of the accessibility of Islamic literature that is more practical and inclusive for a wide audience. However, this phenomenon also presents serious challenges in the form of a shift of religious authority from sanad-based legitimacy to algorithmic validation, the risk of simplification of meaning, and the potential spread of invalid interpretations. Evaluation of automated systems (AI) even shows a low consistency limitation compared to the decisions of scholars. This study concludes the importance of harmonious integration between authentic traditional methods and modern technology, as well as the need to strengthen Islamic digital literacy and the active role of religious institutions to maintain the authenticity of interpretation in cyberspace.   Keywords: Tafsir Al-Qur'an, Digital Era, Islamic Tradition, Innovation, Islamic Literacy.